2007
DOI: 10.1029/2006jd007208
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations of the atmospheric nitrous oxide concentration and its δ15N and δ18O for the latter half of the 20th century reconstructed from firn air analyses

Abstract: Histories of atmospheric N2O concentration and its δ15N and δ18O were reconstructed for the period 1952–2001 on the basis of the analyses of firn air collected at the North Greenland Ice Core Project (NGRIP), Greenland, and Dome Fuji and H72, Antarctica. The N2O concentration increased from 290 ppbv in 1952 to 316 ppbv in 2001, which agrees well with the results from atmospheric observations and polar ice core analyses. The δ15N and δ18O showed a secular decrease, the respective values being 8.9 and 21.5‰ in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(129 citation statements)
references
References 53 publications
6
112
3
Order By: Relevance
“…Temporal trends in the N 2 O isotopic composition from firn air, ice core and archived air sample measurements indicate a year to year decrease in δ 15 N bulk of 0.04 ‰ yr −1 , confirming substantial emissions of isotopically depleted N 2 O (Bernard et al, 2006;Ishijima et al, 2007;Röckmann and Levin, 2005). According to isotopic budgetary calculations based on a simple twobox model, this could be due to increased anthropogenic N 2 O emission from agricultural soils, as well as a to a change in their average isotopic signature (Ishijima et al, 2007).…”
Section: Introductionmentioning
confidence: 88%
“…Temporal trends in the N 2 O isotopic composition from firn air, ice core and archived air sample measurements indicate a year to year decrease in δ 15 N bulk of 0.04 ‰ yr −1 , confirming substantial emissions of isotopically depleted N 2 O (Bernard et al, 2006;Ishijima et al, 2007;Röckmann and Levin, 2005). According to isotopic budgetary calculations based on a simple twobox model, this could be due to increased anthropogenic N 2 O emission from agricultural soils, as well as a to a change in their average isotopic signature (Ishijima et al, 2007).…”
Section: Introductionmentioning
confidence: 88%
“…In particular, when the isotopic composition of tropospheric N 2 O is combined with the fractionation during its removal in the stratosphere, the isotopic composition of the global average source can be determined (Ishijima et al, 2007;Bernard et al, 2006;Röckmann et al, 2003b;Kim and Craig, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…For N 2 O, a number of studies have reported isotope measurements from different Arctic and Antarctic firn drilling sites, showing a steady decrease in the heavy isotope content of N 2 O over the past decades Ishijima et al, 2007;Bernard et al, 2006;Röckmann et al, 2003b;Sowers et al, 2002). A more recent study by Park et al (2012) attempted to reconstruct the long-term trends in N 2 O isotopic compositions and its seasonal cycles to further distinguish between the influence of the stratospheric sink and the oceanic source at Cape Grim, Tasmania, demonstrating that isotope measurements can help in the attribution and quantification of surface sources in general.…”
Section: Introductionmentioning
confidence: 99%
“…Isotopes of N 2 O ( 15 N and 18 O) measured in firn air and ice show decreasing values (Sowers et al 2002;Ishijima et al 2007) that are considered to be consistent with an increasing importance of agriculture (and in particular the use of fertilizers) for N 2 O (Sowers et al 2002). Recently, the first measurements of position-dependent 15 N in firn air and ice have been reported along with further data for 18 O (Bernard et al 2006).…”
Section: The Last 2000 Yearsmentioning
confidence: 94%